Thermoplastic resin composition, its manufacturing method and molded article manufactured therefrom

JP7636572B2Active Publication Date: 2025-02-26LG CHEM LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023552104
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-01-05
Publication Date
2025-02-26
Estimated Expiration
2043-01-05

AI Technical Summary

Benefits of technology

【0032】 本発明によれば、非ハロゲンリン系難燃剤を使用して高難燃性を実現し、(D)ホスファイト(phosphite)系熱安定剤と(E)銅系複合熱安定剤の組み合わせによって、含湿後にも機械的物性及び電気的物性がいずれも優れたシナジー効果が発現されるため、自動車部品、電気·電子部品などに高品質で適用できる熱可塑性樹脂組成物、その製造方法及びそれを含む成形品を提供する効果がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636572000001
    Figure 0007636572000001
  • Figure 0007636572000002
    Figure 0007636572000002
  • Figure 0007636572000003
    Figure 0007636572000003
Patent Text Reader

Abstract

The present disclosure relates to a thermoplastic resin composition, a method for producing the same, and a molded article containing the same. More specifically, the present disclosure relates to a thermoplastic resin composition comprising: (A) 35 to 65% by weight of a polyamide resin; (B) 18 to 40% by weight of glass fiber; (C) 10 to 30% by weight of a composite flame retardant; (D) 0.06 to 0.4% by weight of a phosphite-based heat stabilizer; and (E) 0.1 to 0.7% by weight of a copper-based composite heat stabilizer; a method for producing the same, and a molded article containing the same. According to the present invention, there are provided a thermoplastic resin composition which realizes high flame retardancy by using a non-halogen phosphorus-based flame retardant and has excellent mechanical and electrical properties even after moisture absorption, a production method thereof, and a molded article containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0011269 filed on January 26, 2022 and Korean Patent Application No. 10-2023-0001114 refiled on January 4, 2023 based thereon, and all contents disclosed in the documents of the Korean patent application are incorporated as part of this specification.

[0002] The present invention relates to a thermoplastic resin composition, a manufacturing method thereof, and a molded article containing the same. More specifically, the present invention relates to a thermoplastic resin composition that achieves high flame retardancy by using a non-halogen phosphorus-based flame retardant and has excellent mechanical and electrical properties even after absorbing moisture, a manufacturing method thereof, and a molded article containing the same. [Background technology]

[0003] Polyamide resin, a type of engineering plastic, is a crystalline and thermoplastic material that has excellent mechanical strength, abrasion resistance, heat resistance, chemical resistance, electrical insulation, and arc resistance, and is therefore widely used in various fields such as automobile parts, electrical and electronic parts, and various industrial materials. However, polyamide resin has a high moisture absorption rate due to the amide bond in the resin, and the mechanical and electrical properties are severely deteriorated by the absorbed moisture, which limits its range of application.

[0004] Furthermore, since polyamide resins themselves have low flame retardancy, flame retardants are used in fields where flame retardancy is required.

[0005] In recent years, in accordance with the European REACH and RoHS regulations, active research has been conducted into replacing the brominated flame retardants used in polyamide resin compositions with non-halogen flame retardants.

[0006] Among non-halogen flame retardants, phosphorus-based flame retardants have the advantage of achieving the highest level of flame retardancy, such as a Glow Wire Flammability Index (GWFI) of 960℃ and a Comparative Tracking Index (CTI) of 600V, when applied in the same amount as existing bromine-based flame retardants. However, they are more expensive than bromine-based flame retardants, which leads to increased costs.

[0007] Nitrogen-based flame retardants, which are another type of non-halogen flame retardant, achieve flame retardancy in a different way than bromine-based and phosphorus-based flame retardants. Bromine-based and phosphorus-based flame retardants achieve flame retardancy by forming char on the outside of the polymer when burned by a heat source, blocking the inflow of oxygen and heat, whereas nitrogen-based flame retardants achieve flame retardancy by inducing the breakdown of the polymer and dripping of the material itself when they receive energy from a heat source.

[0008] In general, nitrogen-based flame retardants cannot be used with inorganic filler reinforcing materials such as glass fiber because the glass fiber acts as a support inside the polymer, preventing the polymer from collapsing and reducing the exhaustibility of the material. As a result, when inorganic filler reinforcing materials are used together with nitrogen-based flame retardants, the GWFI is only 600°C or less and the CTI is only 500V or less, resulting in poor electrical properties and flame retardancy.

[0009] In addition, a copper-based composite heat stabilizer is used to improve electrical properties, but there is a problem in that the electrical properties are significantly degraded after moisture absorption.

[0010] Therefore, there is a need to develop a thermoplastic resin composition that can realize high flame retardancy using a non-halogen flame retardant and can be used under humid conditions because it has excellent mechanical and electrical properties even after absorbing moisture. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] Korean Patent Publication No. 10-2014-0086795 Summary of the Invention [Problem to be solved by the invention]

[0012] In order to solve the problems of the prior art as described above, the present disclosure aims to provide a thermoplastic resin composition that realizes high flame retardancy by using a non-halogen phosphorus-based flame retardant and has excellent mechanical and electrical properties even after moisture absorption.

[0013] Another object of the present disclosure is to provide a method for producing the thermoplastic resin composition.

[0014] Another object of the present disclosure is to provide a molded article produced from the thermoplastic resin composition.

[0015] The above and other objects of the present disclosure can all be achieved by the disclosure as set forth below. [Means for solving the problem]

[0016] In order to achieve the above object, the present disclosure provides a thermoplastic resin composition comprising: (A) 35 to 65 weight % of a polyamide resin; (B) 18 to 40 weight % of glass fiber; (C) 10 to 30 weight % of a composite flame retardant; (D) 0.06 to 0.4 weight % of a phosphite-based heat stabilizer; and (E) 0.1 to 0.7 weight % of a copper-based composite heat stabilizer.

[0017] Preferably, the thermoplastic resin composition may have a Comparative Tracking Index (CTI) of 530 V or more, measured on a 3 mm thick test piece according to IEC 60112, after being impregnated in a water bath at 70° C. for 7 days.

[0018] Preferably, the thermoplastic resin composition may contain 0.01 to 0.6% by weight of a nucleating agent (F) relative to the total weight of the thermoplastic resin composition.

[0019] Preferably, the (F) nucleating agent may be one or more organic nucleating agents selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, or salts or esters thereof; one or more inorganic nucleating agents selected from the group consisting of talc, mica, wollastonite, silica, kaolin, and clay; or a mixture thereof.

[0020] Preferably, the (A) polyamide resin may be one or more selected from the group consisting of a polymer of a diamine having 2 to 30 carbon atoms and a dicarboxylic acid having 4 to 30 carbon atoms; a lactam polymer; an aminocarboxylic acid polymer; and a copolymer of a lactam and an aminocarboxylic acid.

[0021] Preferably, the (B) glass fibers may have an average diameter of 3 to 25 μm and an average length of 1 to 10 mm.

[0022] Preferably, the (C) composite flame retardant may include (c-1) an organic phosphinate metal salt and (c-2) a melamine phosphate flame retardant.

[0023] Preferably, the (c-1) organic phosphinate metal salt may be a compound represented by the following chemical formula 1.

[0024] [ka] (The R1 and R2 are each an alkyl group or an aryl group having 1 to 6 carbon atoms, M is one or more selected from the group consisting of Mg, Ca, Al, Sb, Sn, Ge, Ti, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, and a protonated nitrogen base, and the n is an integer of 1 to 4.)

[0025] Preferably, the (c-2) melamine phosphate-based flame retardant may be at least one selected from the group consisting of melamine pyrophosphate, melamine polyphosphate, melamine pyrophosphate metal salts, and cyclic benzyl phosphate.

[0026] Preferably, the (D) phosphite-based heat stabilizer may be one or more selected from the group consisting of triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl-di-tridecyl) phosphite, cyclic neopentanetetrayl-bis(octadecyl) phosphite, tris(nonylphenyl) phosphite, tris(dinonyl) phosphite, dioctadecyl-3,5-di-t-butyl-4-hydroxybenzyl phosphonate, and di-n-octadecyl-1-(3,5-di-t-butyl-4-hydroxy-phenyl)-ethane phosphonate.

[0027] Preferably, the (D) phosphite-based heat stabilizer may have a phosphorus content of 8 to 13% by weight based on the total weight of the phosphite-based heat stabilizer.

[0028] Preferably, the (E) copper-based composite heat stabilizer may be at least one selected from the group consisting of copper chloride (I), copper bromide (I), copper iodide (I), copper chloride (II), copper bromide (II), and copper iodide (II).

[0029] Preferably, the (E) copper-based composite heat stabilizer may contain an alkali metal halide.

[0030] The present disclosure also provides a method for producing a thermoplastic resin composition, comprising the steps of kneading and extruding a mixture containing 35 to 65 weight % of (A) polyamide resin, 18 to 40 weight % of (B) glass fiber, 10 to 30 weight % of (C) composite flame retardant, 0.06 to 0.4 weight % of (D) phosphite-based heat stabilizer, and 0.1 to 0.7 weight % of (E) copper-based composite heat stabilizer under conditions of 220 to 280°C and 100 to 400 rpm to produce the mixture into pellets.

[0031] The present disclosure also provides a molded article comprising the thermoplastic resin composition. Effect of the Invention

[0032] According to the present invention, a non-halogen phosphorus-based flame retardant is used to realize high flame retardancy, and a combination of a phosphite-based heat stabilizer (D) and a copper-based composite heat stabilizer (E) provides excellent synergistic effects in both mechanical and electrical properties even after moisture absorption, and therefore, a thermoplastic resin composition that can be used with high quality in automobile parts, electric and electronic parts, a manufacturing method thereof, and a molded product containing the same are provided.

[0033] In particular, the thermoplastic resin composition of the present invention has the effect of being applicable to connectors, circuit breaker products, etc., since it maintains its mechanical properties and electrical properties under humid conditions. BEST MODE FOR CARRYING OUT THEINVENTION

[0034] The thermoplastic resin composition of the present invention, its production method and molded articles containing the same will be described in detail below.

[0035] The present inventors have confirmed that when a polyamide resin, glass fiber, and composite flame retardant are mixed with a phosphite-based heat stabilizer and a copper-based composite heat stabilizer in a predetermined amount, the non-halogen phosphorus-based flame retardant achieves high flame retardancy, has excellent appearance quality, and has improved mechanical and electrical properties to similar or equivalent levels even after moisture absorption. Based on this, the inventors have further pursued research and completed the present invention.

[0036] The thermoplastic resin composition according to the present invention will be described in detail as follows.

[0037] The thermoplastic resin composition of the present invention is characterized by comprising: (A) 35 to 65 weight percent of polyamide resin; (B) 18 to 40 weight percent of glass fiber; (C) 10 to 30 weight percent of composite flame retardant; (D) 0.06 to 0.4 weight percent of a phosphite-based heat stabilizer; and (E) 0.1 to 0.7 weight percent of a copper-based composite heat stabilizer. In this case, the non-halogen phosphorus-based flame retardant is used to achieve high flame retardancy, and the composition has the advantage of having excellent mechanical and electrical properties even after moisture absorption.

[0038] Hereinafter, the thermoplastic resin composition of the present invention will be described in detail with respect to each component.

[0039] (A) Polyamide resin The (A) polyamide resin may be contained in an amount of, for example, 35 to 65% by weight, preferably 40 to 60% by weight, more preferably 45 to 55% by weight, and even more preferably 45 to 51% by weight, based on the total weight of the (A) to (E) components. Within this range, there is an advantage in that the physical properties, such as mechanical strength, extrusion processability, and appearance quality, are well balanced.

[0040] The polyamide resin (A) is not particularly limited, but may be a polyamide produced by condensation polymerization of a lactam or an ω-amino acid, or two or more kinds of them, or a polyamide produced by condensation polymerization of a diacid and a diamine.

[0041] Preferably, the (A) polyamide resin is at least one selected from the group consisting of a polymer of a diamine having 2 to 30 carbon atoms and a dicarboxylic acid having 4 to 30 carbon atoms; a lactam polymer; an aminocarboxylic acid polymer; and a copolymer of a lactam and an aminocarboxylic acid. In this case, there is an effect of excellent mechanical properties and appearance quality.

[0042] Moreover, the (A) polyamide resin may be, for example, a homopolyamide, a copolyamide, or a mixture thereof.

[0043] The (A) polyamide resin may be, for example, crystalline, semi-crystalline or amorphous.

[0044] The polymer of a diamine having 2 to 30 carbon atoms and a dicarboxylic acid having 4 to 30 carbon atoms is preferably a polymer of an aliphatic or aromatic diamine such as ethylenediamine, tetramethylenediamine, hexamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, 5-methylnonahexamethylenediamine, metaxylenediamine, paraxylenediamine, 1,3-bisaminomethylcyclohexane, 1,4-bisaminomethylcyclohexane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, bis(4-aminocyclohexane)methane, bis(4-methyl-4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminopropyl)piperazine, or aminoethylpiperidine, and adipic acid, sebacic acid, or the like. The polyamide may be one or more polymers selected from the group consisting of polyamides obtained by polymerization with aliphatic or aromatic dicarboxylic acids such as terephthalic acid, azelaic acid, terephthalic acid, 2-chloroterephthalic acid, and 2-methylterephthalic acid.

[0045] The lactam polymer may be obtained by ring-opening polymerization of a lactam compound such as caprolactam or laurolactam.

[0046] The amino carboxylic acid polymer may be obtained by polymerizing an amino carboxylic acid such as aminocaproic acid, 11-aminoundecanoic acid, or 12-aminododecanoic acid.

[0047] The polyamide resin may preferably include one or more selected from the group consisting of polyamide 6, polyamide 66, polyamide 46, polyamide 11, polyamide 12, polyamide 610, polyamide 612, polyamide 6 / 66, polyamide 6 / 612, polyamide MXD6, polyamide 6 / MXD6, polyamide 66 / MXD6, polyamide 6T, polyamide 6I, polyamide 6 / 6T, polyamide 6 / 6I, polyamide 66 / 6T, polyamide 66 / 6I, polyamide 6 / 6T / 6I, polyamide 66 / 6T / 6I, polyamide 9T, polyamide 9I, polyamide 6 / 9T, polyamide 6 / 9I, polyamide 66 / 9T, polyamide 6 / 12 / 9T, polyamide 66 / 12 / 9T, polyamide 6 / 12 / 9I, and polyamide 66 / 12 / 6I.

[0048] The (A) polyamide resin may more preferably be polyamide 6. In this case, not only is it advantageous in terms of cost and processability, but it also has the advantage of improving mechanical properties and heat resistance.

[0049] The (A) polyamide resin may have, for example, a relative viscosity (RV) of 2 to 3, preferably 2.1 to 2.7, and more preferably 2.2 to 2.5. In this case, there is an advantage that the problem of overheating due to friction between the extruder screw and the molten composition during extrusion molding does not occur, and the tension applied to the molten composition is appropriate, resulting in excellent extrusion processability.

[0050] In this description, the relative viscosity is measured with a UFIT-UVS instrument at 20° C. using a solution prepared by dissolving 1 g of polyamide in 100 ml of 96% by weight sulfuric acid, unless otherwise stated.

[0051] The (A) polyamide resin may have a number average molecular weight of, for example, 10,000 to 500,000 g / mol, preferably 10,000 to 300,000 g / mol, more preferably 10,000 to 180,000 g / mol, and even more preferably 10,000 to 100,000 g / mol. Within this range, there is an advantage in that the resin has excellent moldability while having an excellent balance of physical properties.

[0052] In this description, unless otherwise specified, the number average molecular weight is a value measured by gel permeation chromatography at 40°C, specifically, by dissolving 10 mg of resin in 10 g of hexafluoroisopropanol, and using polymethyl methacrylate (PMMA) as the standard substance. At this time, as a specific measurement example, the measurement can be performed under the following conditions: solvent: hexafluoroisopropanol, column temperature: 40°C, flow rate: 0.3ml / min, sample concentration: 20mg / ml, injection amount: 5μl, column model: 1×PLgel 10μm MiniMix-B (250×4.6mm)+1×PLgel 10μm MiniMix-B (250×4.6mm)+1×PLgel 10μm MiniMix-B Guard (50×4.6mm), equipment name: Agilent 1200 series system, refractive index detector: Agilent G1362 RID, RI temperature: 35°C, data processing: Agilent ChemStation S / W, test method (Mn, Mw and PDI): OECD TG 118.

[0053] The method for producing the polyamide resin (A) is not particularly limited as long as it is a production method commonly applied in this technical field, and commercially available products may be used.

[0054] (B) Glass fiber The (B) glass fiber is included for the purpose of reinforcing the mechanical properties of the composition at low cost, and may be included in an amount of, for example, 18 to 40% by weight, preferably 22 to 38% by weight, and more preferably 27 to 33% by weight, based on the total weight of the (A) to (E) components. Within this range, there are advantages in that the mechanical properties are improved without impairing processability, and the final product has excellent appearance characteristics.

[0055] The (B) glass fiber may have an average diameter of, for example, 3 to 25 μm, preferably 5 to 20 μm, and more preferably 7 to 15 μm. Within this range, the mechanical strength is improved and the appearance characteristics of the final product are excellent.

[0056] The (B) glass fiber may have an average length of, for example, 1 to 10 mm, preferably 1 to 7 mm, and more preferably 2 to 5 mm. Within this range, the mechanical strength is improved and the appearance characteristics of the final product are excellent.

[0057] The (B) glass fiber may have, for example, an aspect ratio (L / D), which is the ratio of the average length (L) to the average diameter (D), of 100 to 550, preferably 150 to 500, and more preferably 200 to 400. Within this range, the glass fiber has excellent compatibility with resins, and thus has the advantage of excellent surface appearance.

[0058] In this description, the average diameter and the average length of glass fibers are calculated by averaging 30 pieces measured by microscopic analysis.

[0059] The (B) glass fiber may be, for example, chopped glass fiber.

[0060] In the present description, the chopped glass fiber is not particularly limited as long as it is a chopped fiber glass commonly used in the technical field to which the present invention pertains.

[0061] The (B) glass fiber may be, for example, surface-treated with one or more surface treatment agents selected from the group consisting of aminosilane-based compounds, epoxysilane-based compounds, and urethanes. In this case, it provides the advantage of improving compatibility and dispersing uniformly within the composition to further improve mechanical strength.

[0062] The surface treatment agent may be contained in an amount of, for example, 0.1 to 10% by weight, preferably 0.1 to 5% by weight, more preferably 0.1 to 0.8% by weight, and even more preferably 0.2 to 0.5% by weight, relative to a total of 100% by weight (glass fiber + surface treatment agent) of the surface-treated glass fiber. Within this range, the effect of excellent mechanical properties, friction and wear resistance, and balance of physical properties is achieved.

[0063] The aminosilane compound is not particularly limited as long as it is an aminosilane that is generally used as a coating agent for glass fibers. For example, it may be at least one selected from the group consisting of γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, γ-acetoacetatepropyltrimethoxysilane, γ-acetoacetatepropyltriethoxysilane, γ-cyanoacetyltrimethoxysilane, γ-cyanoacetyltriethoxysilane, and acetoxyacetotrimethoxysilane. In this case, there is an effect that the surface properties of the extruded product are excellent while the mechanical properties and thermal properties are excellent.

[0064] The epoxy silane compound is not particularly limited as long as it is an epoxy silane that is generally used as a coating agent for glass fibers. For example, the epoxy silane compound may be at least one selected from the group consisting of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-glycidyloxypropyl(dimethoxy)methylsilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. In this case, the epoxy silane compound has an effect of providing excellent surface properties of the extruded product while providing excellent mechanical properties and heat resistance.

[0065] The (B) glass fiber may be appropriately selected from the range of ordinary use in the art as long as it complies with the definition of the present invention, and the cross-sectional shape, such as cylindrical or elliptical, is not particularly limited.

[0066] (C) Complex flame retardants The (C) composite flame retardant may be contained in an amount of, for example, 10 to 30% by weight, preferably 15 to 25% by weight, and more preferably 17 to 23% by weight, based on the total weight of the (A) to (E) components. Within this range, a small content can achieve high flame retardancy and excellent mechanical properties.

[0067] The (C) composite flame retardant may, for example, include (c-1) an organic phosphinate metal salt and (c-2) a melamine phosphate flame retardant. In this case, it has the effect of realizing high flame retardancy and excellent mechanical properties with a small content.

[0068] The weight ratio (c-1:c-2) of the (c-1) organic phosphinate metal salt and (c-2) melamine phosphate flame retardant may be, for example, 60:40 to 90:10, preferably 65:35 to 85:15, and more preferably 70:30 to 80:20. Within this range, there is an advantage in that excellent flame retardancy and physical properties can be balanced.

[0069] The (c-1) organic phosphinate metal salt may be, for example, a compound represented by the following formula 1. In this case, it has the effect of providing excellent flame retardancy and excellent balance of physical properties.

[0070] [ka] (The R1 and R2 are each an alkyl group or an aryl group having 1 to 6 carbon atoms, M is one or more selected from the group consisting of Mg, Ca, Al, Sb, Sn, Ge, Ti, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, and a protonated nitrogen base, and the n is an integer of 1 to 4.)

[0071] The (c-1) organic phosphinate metal salt is preferably at least one selected from the group consisting of aluminum phosphinate, calcium phosphinate, and zinc phosphinate, more preferably aluminum ethyl methyl phosphinate, aluminum diethyl phosphinate, or a mixture thereof, and even more preferably aluminum diethyl phosphinate, which has the advantage of providing a good balance between excellent flame retardancy and physical properties.

[0072] The (c-2) melamine phosphate-based flame retardant may be, for example, at least one selected from the group consisting of melamine pyrophosphate, melamine polyphosphate, melamine pyrophosphate metal salt, and cyclic benzyl phosphate, and is preferably melamine polyphosphate. In this case, there is an effect of increasing flame retardancy and improving flame dripping.

[0073] The (C) composite flame retardant has the advantage that a synergistic effect of flame retardancy is exhibited and mechanical properties are excellent by using the (c-1) organic phosphinate metal salt and the (c-2) melamine phosphate flame retardant in combination.

[0074] (D) Phosphite-based heat stabilizers The (D) phosphite-based heat stabilizer may be included in an amount of, for example, 0.06 to 0.4 wt %, preferably 0.1 to 0.3 wt %, and more preferably 0.1 to 0.25 wt %, based on the total weight of the (A) to (E) components. Within this range, the composition has excellent mechanical and electrical properties after moisture absorption, and if the amount exceeds this range, the composition acts as an impurity in the thermoplastic resin composition, thereby deteriorating the mechanical properties.

[0075] The (D) phosphite-based heat stabilizer may be, for example, one or more selected from the group consisting of triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl-di-tridecyl) phosphite, cyclic neopentanetetrayl-bis(octadecyl) phosphite, tris(nonylphenyl) phosphite, tris(dinonyl) phosphite, dioctadecyl-3,5-di-t-butyl-4-hydroxybenzyl phosphonate, and di-n-octadecyl-1-(3,5-di-t-butyl-4-hydroxy-phenyl)-ethane phosphonate, and preferably triphenyl phosphite. In this case, by combining with the (E) copper-based composite heat stabilizer described later, there is an advantage that both electrical performance before and after humidification are improved.

[0076] The (D) phosphite-based heat stabilizer may, for example, have a phosphorus content of 5 to 15% by weight based on the total weight of the stabilizer. Preferably 8 to 13% by weight, More preferably, it may be 7 to 13% by weight, in which case there is an effect of providing excellent flame retardancy as well as excellent impact resistance.

[0077] In this description, the phosphorus content means the weight % of phosphorus calculated from the molecular weight of phosphorus contained in the molecular structure of the phosphite-based heat stabilizer.

[0078] The (D) phosphite-based heat stabilizer is more preferably triphenyl phosphite having a phosphorus content of 5 to 15 wt % based on the total weight of the stabilizer. In this case, when combined with the (E) copper-based composite heat stabilizer described later, it has the advantage that the electrical performance before and after absorbing moisture is improved.

[0079] (E) Copper-based composite heat stabilizer The (E) copper-based composite heat stabilizer may be included in an amount of, for example, 0.1 to 0.7% by weight, preferably 0.2 to 0.6% by weight, and more preferably 0.2 to 0.5% by weight, based on the total weight of the (A) to (E) components, and within this range, by combining with the (D) phosphite-based heat stabilizer, there is an advantage that the mechanical properties and electrical properties are excellent both before and after moisture absorption, and when the amount exceeds this range, it acts as an impurity in the thermoplastic resin composition and reduces the mechanical properties. The (E) copper-based composite heat stabilizer has the effect of improving electrical properties more when used together with the (D) phosphite-based heat stabilizer than when used alone.

[0080] The (E) copper-based composite heat stabilizer is, for example, at least one selected from the group consisting of copper chloride (I), copper bromide (I), copper iodide (I), copper chloride (II), copper bromide (II) and copper iodide (II), and is preferably copper iodide (I). In this case, there is an advantage in that it prevents deterioration of mechanical properties and electrical properties after absorbing moisture.

[0081] Preferably, the (E) copper-based composite heat stabilizer can be used together with an alkali metal halide, and in this case, there is an advantage that the mechanical properties and electrical properties are more excellent after absorbing moisture.

[0082] The alkali metal halide may be, for example, at least one selected from the group consisting of lithium chloride, lithium bromide, lithium iodide, sodium fluoride, sodium chloride, sodium bromide, sodium iodide, potassium fluoride, potassium chloride, potassium bromide, and potassium iodide, and preferably at least one selected from the group consisting of potassium bromide and potassium iodide. In this case, there is an advantage in that the mechanical properties and electrical properties are excellent after humidification.

[0083] The (E) copper-based composite heat stabilizer may have a copper content of 50 to 150 ppm, preferably 80 to 130 ppm, and more preferably 90 to 120 ppm, based on the total weight of the stabilizer. Within this range, there is an advantage in preventing deterioration of mechanical properties and electrical properties after moisture absorption.

[0084] In this description, the copper content in the copper-based composite heat stabilizer is measured using an X-ray fluorescence analyzer under WDXRF (Wavelength Dispersive X-ray Fluorescence) or EDXRF (Energy Dispersive X-ray Fluorescence) conditions.

[0085] In the present invention, the combination of the (D) phosphite-based heat stabilizer and the (E) copper-based composite heat stabilizer induces a dipole-dipole interaction between the chain structure of the polyamide resin and moisture, or exists as a ligand structure, thereby generating a synergistic effect that minimizes the deterioration of electrical properties caused by the water-soluble copper salt not coming out to the surface of the material when exposed to a humid environment with sufficient moisture.

[0086] (Additives) (F) Nucleating agent The thermoplastic resin composition may contain, for example, a nucleating agent (F).

[0087] The nucleating agent (F) may be contained in an amount of, for example, 0.01 to 0.6% by weight, preferably 0.05 to 0.5% by weight, more preferably 0.1 to 0.3% by weight, based on the total weight of the components (A) to (E) and the component (F). Within this range, the bonding strength between the polyamide resin and the glass fiber increases, the crystallinity of the polyamide resin increases, and the deterioration of mechanical and electrical properties due to moisture absorption is suppressed, resulting in excellent surface appearance. On the other hand, if the amount exceeds the range, it acts as an impurity in the thermoplastic resin composition and deteriorates the mechanical properties.

[0088] The (F) nucleating agent is, for example, one or more selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, or salts or esters thereof. Phosphorus-containing The nucleating agent may be one or more inorganic nucleating agents selected from the group consisting of talc, mica, wollastonite, silica, kaolin, and clay; or a mixture thereof. In this case, the mechanical properties and electrical properties are improved.

[0089] The (F) nucleating agent is preferably Phosphorus-containing It may be a nucleating agent, in which case there is an effect of providing excellent surface appearance.

[0090] The above Phosphorus-containing The nucleating agent is preferably at least one selected from the group consisting of sodium phosphate, sodium phosphite, sodium hypophosphite, and potassium phosphite, and may be more preferably sodium phosphate. In this case, there are advantages in that the bonding strength between the polyamide resin and the glass fiber is increased, the crystallinity of the polyamide resin is increased, deterioration of mechanical properties and electrical properties due to moisture absorption is suppressed, and the surface appearance is excellent.

[0091] The (F) nucleating agent may be included in an amount equal to or less than that of the (E) copper-based composite heat stabilizer, and in this case, the mechanical and electrical properties before and after impregnation are more excellent.

[0092] (G) Lubricant The thermoplastic resin composition may contain, for example, (G) a lubricant.

[0093] The (G) lubricant may be contained in an amount of, for example, 0.01 to 1% by weight, preferably 0.05 to 0.7% by weight, and more preferably 0.1 to 0.6% by weight, based on the total weight of the (A) to (E) components and the (G) lubricant. Within this range, compatibility with the polyamide resin is enhanced, thereby reducing surface defects and improving mechanical properties.

[0094] The (G) lubricant may be, for example, one or more selected from the group consisting of fatty acid amide compounds, montan waxes, and olefin waxes, and preferably one or more selected from the group consisting of fatty acid amide compounds and montan waxes. In this case, by increasing the compatibility with the polyamide resin, there is an effect of reducing the surface defect phenomenon.

[0095] The fatty acid amide compound may be, for example, at least one selected from the group consisting of stearamide, behenamide, ethylene bis(stearamide), N,N'-ethylene bis(12-hydroxy stearamide), erucamide, oleamide, and ethylene bis oleamide.

[0096] The montan wax may be, for example, a montan wax, a montan ester wax, or a mixture thereof.

[0097] The montan ester wax may be at least one selected from, for example, a wax in which a montan wax is esterified with ethylene glycol and montanic acid, a wax in which a montan wax is esterified with glycerin and montanic acid, calcium montanate containing a montanic acid ester, and an ester mixed wax based on montanic acid.

[0098] The olefin wax may be, for example, a polyethylene wax, a polypropylene wax, or a mixture thereof.

[0099] The thermoplastic resin composition may further contain, for example, 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, more preferably 0.1 to 2 parts by weight, and even more preferably 0.2 to 1.5 parts by weight of one or more selected from the group consisting of antioxidants, ultraviolet absorbers, heat stabilizers, antistatic agents, anti-dripping agents, antibacterial agents, processing aids, anti-friction agents, anti-wear agents, metal deactivators, coupling agents, pigments, and dyes, based on 100 parts by weight of the total of the components (A) to (E). Within these ranges, there is an effect that the required physical properties are well realized while the inherent physical properties of the thermoplastic resin composition described herein are not deteriorated.

[0100] (Thermoplastic resin composition) The thermoplastic resin composition may preferably have a Comparative Tracking Index (CTI) of 530 V or more, more preferably 550 V or more, and even more preferably 550 to 750 V after being immersed in a water bath at 70° C. for 7 days and then moistened, as measured on a 3 mm thick test piece in accordance with IEC 60112. Within this range, the composition has an excellent balance of physical properties and is advantageously applicable to automobiles and electric / electronic parts used under moist conditions.

[0101] The thermoplastic resin composition may preferably have a Comparative Tracking Index (CTI) of 550 V or more, more preferably 600 V or more, and even more preferably 600 to 800 V, measured on a 3 mm thick test piece in accordance with IEC 60112 before impregnation. Within this range, the composition has the effect of having an excellent balance of physical properties and excellent electrical properties.

[0102] The thermoplastic resin composition preferably has a Charpy impact strength of 15 kJ / m after immersion in a water bath at 70° C. for 7 days, measured at room temperature on a 4 mm thick test piece in accordance with ISO 179. 2 More preferably, 17 kJ / m 2 More preferably, 20 kJ / m 2 More preferably, 20 to 30 kJ / m 2 Within this range, there is an advantage that the physical properties are well balanced and the molded product can be applied to a molded product to be used under humid conditions.

[0103] In this description, normal temperature may be a point within the range of 20±5°C.

[0104] The thermoplastic resin composition preferably has a Charpy impact strength of 8 kJ / m, measured at room temperature on a 4 mm thick test piece according to ISO 179, before impregnation. 2 More preferably, 9 kJ / m 2 More preferably, 9 to 15 kJ / m 2 Within this range, the effect of achieving a good balance of physical properties and excellent mechanical properties is obtained.

[0105] The thermoplastic resin composition may preferably have a tensile strength of 70 MPa or more, more preferably 73 MPa or more, even more preferably 75 MPa or more, and even more preferably 75 to 100 MPa after being immersed in a water bath at 70°C for 7 days and then moistened, as measured in accordance with ISO 527-1 and ISO 527-2 using a 4 mm thick test piece at a cross head speed of 5 mm / min. Within this range, the composition has an excellent balance of physical properties and is advantageously applicable to automobiles and electric / electronic parts used under moist conditions.

[0106] The thermoplastic resin composition may preferably have a tensile strength of 130 MPa or more, more preferably 135 MPa or more, even more preferably 137 MPa or more, and even more preferably 137 to 150 MPa, measured before impregnation using a 4 mm thick test piece at a cross head speed of 5 mm / min in accordance with ISO 527-1 and ISO 527-2. Within this range, the thermoplastic resin composition has an excellent balance of physical properties and excellent mechanical properties, and thus has the effect of being applicable to automobile parts and electric / electronic parts with high quality.

[0107] The thermoplastic resin composition may preferably have a tensile elongation after immersion in a water bath at 70°C for 7 days, measured in accordance with ISO 527-1 and ISO 527-2 using a 4 mm thick test piece at a cross head speed of 5 mm / min, of 7.5% or less, more preferably 7% or less, even more preferably 6.7% or less, and even more preferably 3 to 6.7%. Within this range, the thermoplastic resin composition has excellent mechanical properties and a good balance of physical properties, and is advantageous in that it can be applied to automobiles and electric / electronic parts used under humid conditions.

[0108] The thermoplastic resin composition may preferably have a tensile elongation of 1.5% or more, more preferably 1.8% or more, and even more preferably 1.8 to 2.4%, as measured before impregnation using a 4 mm thick test piece at a cross head speed of 5 mm / min in accordance with ISO 527-1 and ISO 527-2. Within this range, the composition has the effect of exhibiting excellent balance of physical properties and excellent mechanical properties.

[0109] The thermoplastic resin composition may preferably have a heat distortion temperature of 205°C or higher, more preferably 208°C or higher, and even more preferably 208°C to 220°C, measured before impregnation on a 4 mm thick test piece in the flatwise direction under a load of 1.80 MPa in accordance with ISO 75-1 or ISO 75-2. Within this range, there is an advantage in that the composition has excellent balance of physical properties and heat resistance.

[0110] The thermoplastic resin composition may preferably have a Glow Wire Flammability Index (GWFI) of 960° C. or more, measured on a test piece having a thickness of 1.5 mm in accordance with IEC 60695-2-12, before impregnation. In this case, there is an advantage in that the physical property balance and flame retardancy are excellent.

[0111] In this document, the Glow Wire Flammability Index (GWFI) is a flame retardancy standard required for engineering plastics used in the electrical and electronic fields in addition to the flame retardancy standard based on the UL94 standard, which allows for more accurate understanding of flame retardancy behavior and prevents fires from occurring. The UL94 flame retardancy evaluation method uses flame as a heat source to mimic flame retardancy behavior on the premise that a fire has already occurred, while the International Electrotechnical Commission (IEC) standard Glow Wire Flammability Index (GWFI) can be considered an advanced flame retardancy test method that takes safety into consideration when a fire occurs by providing a heat source that can cause a fire as a glow wire and understanding the behavior of the glow wire.

[0112] A specific method for measuring the glow-wire flammability index is to contact a glow-wire with a test piece for 30 seconds, and measure the maximum temperature at which the flame is extinguished within 30 seconds after removing the glow-wire.

[0113] The thermoplastic resin composition preferably has a flame retardancy rating of V-0 or higher as measured on a test piece having a thickness of 0.8 mm in accordance with UL94 after being immersed in a water bath at 70°C for 7 days. Within this range, the composition has an excellent balance of physical properties and is advantageous in that it can be applied to molded articles used under humid conditions.

[0114] The thermoplastic resin composition preferably has a flame retardancy rating of V-0 or higher as measured on a test piece having a thickness of 0.8 mm in accordance with UL94 before impregnation, and in this case, has the advantage of being excellent in balance of physical properties and flame retardancy.

[0115] (Method of producing thermoplastic resin composition) The method for producing a thermoplastic resin composition according to the present invention is characterized by comprising the steps of kneading and extruding 35-65% by weight of (A) polyamide resin, 18-40% by weight of (B) glass fiber, 10-30% by weight of (C) composite flame retardant, 0.06-0.4% by weight of (D) phosphite-based heat stabilizer, and 0.1-0.7% by weight of (E) copper-based composite heat stabilizer under conditions of 220-280°C and 100-400 rpm to produce pellets. In this case, the non-halogen phosphorus-based flame retardant is used to realize high flame retardancy, and the mechanical and electrical properties are excellent even after moisture absorption.

[0116] The kneading and extrusion may be carried out, for example, using a single screw extruder, a twin screw extruder, or a Banbury mixer, and is preferably carried out using a twin screw extruder. In this case, the composition is uniformly dispersed, resulting in excellent compatibility.

[0117] The kneading and extrusion may be carried out, for example, at a barrel temperature in the range of 220 to 280°C, preferably 240 to 260°C. In this case, the processing amount per unit time is appropriate, sufficient melt kneading is possible, and problems such as thermal decomposition of the resin component are not caused.

[0118] The kneading and extrusion may be carried out under conditions where the screw rotation speed is, for example, 100 to 400 rpm, preferably 200 to 400 rpm, and more preferably 250 to 350 rpm. In this case, the processing amount per unit time is appropriate, and thus, the process efficiency is excellent while preventing excessive cutting of the glass fibers.

[0119] The method for producing the thermoplastic resin composition has all the technical features of the thermoplastic resin composition described above, and therefore, the description of the overlapping parts will be omitted.

[0120] (molded product) The molded article described herein is characterized by containing the thermoplastic resin composition described herein. In this case, a non-halogen phosphorus-based flame retardant is used to achieve high flame retardancy, and the molded article has the advantage of having excellent mechanical and electrical properties even after moisture absorption.

[0121] The molded article may preferably be an automobile part or an electric / electronic part, and more preferably may be a connector, a junction box, a charging gun inlet, or a charging gun outlet.

[0122] The method for producing a molded article described herein, for example, is characterized by including the steps of kneading and extruding 35 to 65 weight % of (A) polyamide resin, 18 to 40 weight % of (B) glass fiber, 10 to 30 weight % of (C) composite flame retardant, 0.06 to 0.4 weight % of (D) phosphite-based heat stabilizer, and 0.1 to 0.7 weight % of (E) copper-based composite heat stabilizer at 220 to 280°C and 100 to 400 rpm to produce pellets, and injecting the produced pellets using an injector. In this case, there is an advantage that the method has excellent balance of physical properties while also having excellent injection processability.

[0123] In describing the thermoplastic resin composition, its production method, and molded products, other conditions, equipment, etc. not explicitly described herein can be appropriately selected within the range commonly used in the art, and it is clearly stated that there are no particular limitations.

[0124] Below, preferred examples are presented to aid in understanding the present description. However, the following examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications also fall within the scope of the appended claims.

[0125] [Example] The materials used in the following examples and comparative examples are as follows. *(A) Polyamide resin: Polyamide 6 (relative viscosity 2.3) *(B) Glass fiber: Chopped glass fiber with an average diameter of 9 to 13 μm and an average length of 3 mm, surface-treated with aminosilane. *(C) Composite flame retardant: Aluminum diethylphosphinate (Clariant, OP1230) and melamine polyphosphate (BASF, Melapur200-70) mixed in a weight ratio of 75:25 *(D) Phosphite-based heat stabilizer: Triphenyl phosphite (TPP; phosphorus content 9% by weight) *(E) Copper-based composite heat stabilizer: Mixture of CuI and KI (copper content: 100 ppm) (Crystran's Copper Iodide, Potassium Iodide) *(F-1) Nucleating agent: Sodium phosphate (Bruggemann, P22) *(F-2) Nucleating agent: Talc (KOCH, KC-3000) *(G) Lubricant: Montan wax (Clariant, OP-Wax) *(H) Antioxidant: A mixture of a phenolic antioxidant (N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide) and a phosphite antioxidant (Tris(2,4-di-t-butylphenyl)Phosphite) in a weight ratio of 1:1 (BASF, Irganox B225).

[0126] (Example 1 to 5, 7, 8, Reference examples 6, 9~ 12 and Comparative Examples 1 to 8) (A) polyamide resin, (B) glass fiber, (C) composite flame retardant, (D) phosphite-based heat stabilizer, (E) copper-based composite heat stabilizer, (F) nucleating agent, (G) lubricant, and (H) antioxidant were uniformly mixed in the amounts shown in Tables 1 to 3 below using a Henschel mixer, and extruded using a twin-screw extruder (¢=40mm, L / D=42) at an extrusion temperature of 240 to 260°C and a screw rotation speed of 300 rpm to prepare a pellet-shaped thermoplastic resin composition.

[0127] The prepared pellet-shaped resin composition was dried in a hot air dryer at 120°C for 2 hours or more, and then injection molded using an injection machine (Engel, 80 ton) at an injection temperature of 260°C and a mold temperature of 60°C to prepare test specimens. The test specimens were left in a constant temperature and humidity room (23°C) for 24 hours or more, and then their physical properties were measured and are shown in Tables 1 to 3 below.

[0128] [Test example] The above-mentioned Example 1 5, 7, 8, Reference examples 6, 9~ The properties of the test pieces manufactured in Example 12 and Comparative Examples 1 to 8 were measured by the following methods, and the results are shown in Tables 1 to 3 below.

[0129] (Measurement method) *Tensile strength (MPa): Measured according to ISO 527-1 and ISO 527-2 using a 4 mm thick test piece and a cross head speed of 5 mm / min. * Tensile strength after immersion (MPa): After immersion in a water bath at 70°C for 7 days, the strength was measured on 4 mm thick specimens at a cross head speed of 5 mm / min according to ISO 527-1 and ISO 527-2. *Tensile elongation (%): Measured according to ISO 527 using a 4 mm thick test piece at a cross head speed of 5 mm / min. * Tensile elongation after immersion (%): After immersion in a water bath at 70°C for 7 days, the elongation was measured using a 4 mm thick specimen at a cross head speed of 5 mm / min in accordance with ISO 527-1 and ISO 527-2. *Heat distortion temperature (HDT, °C): Measured in accordance with ISO 75-1 and ISO 75-2 on a 4 mm thick test piece, in the flatwise direction, under a load of 1.80 MPa. *Charpy impact strength (kJ / m 2 ):Measured at room temperature on 4 mm thick test pieces in accordance with ISO 179. * Charpy impact strength after absorbing moisture (kJ / m 2): After immersion in a 70°C water bath for 7 days, measurements were taken at room temperature on 4 mm thick test pieces in accordance with ISO 179. *Comparative Tracking Index (CTI): Measured on a 3 mm thick test piece in accordance with IEC 60112. The unit of the Comparative Tracking Index is V (volts). *Comparative Tracking Index (CTI) after immersion in a 70°C water bath for 7 days, measured on a 3 mm thick test piece in accordance with IEC 60112. *Flame retardancy (UL94): In accordance with UL94, a 0.8mm thick test piece is set vertically and set on fire with a burner. Depending on the extent to which the fire on the test piece goes out naturally within a certain period of time, it is classified into V-2, V-1, and V-0. V-0 is the most excellent in flame retardancy. *Flame retardancy after moisture exposure (UL94): After the test piece was immersed in a water tank at 70°C for 7 days, measurements were taken on a 0.8 mm thick test piece in accordance with UL94. *Glow Wire Flammability Index (GWFI): In accordance with IEC 60695-2-12, a glow wire was placed in contact with a 1.5 mm thick test piece for 30 seconds, and the maximum temperature at which the flame was extinguished within 30 seconds after the glow wire was removed was measured. *Surface appearance: The surface of the injection product having a size of 125 mm x 13 mm x 1 mm was visually observed to see whether glass fiber floating occurred on the surface, and was evaluated as follows. ○: No glass fiber floating on the surface, so the surface appearance is excellent △: Some glass fibers are floating on the surface, and the surface appearance is normal. ×: Glass fibers float on the surface, and the surface appearance is poor.

[0130] [Table 1]

[0131] [Table 2]

[0132] [Table 3]

[0133] As shown in Tables 1 to 3, the thermoplastic resin compositions according to the present invention (Examples 1 to 3) 5, 7, 8, Reference examples 6, 9~ 12) was confirmed to have excellent mechanical properties such as impact strength, tensile strength, and tensile elongation even after moisture absorption, and to have excellent comparative tracking index, GWFI, and flame retardancy, compared with Comparative Examples 1 to 8.

[0134] Here, Examples 1 to 5, 7, 8 and 9 contain (F-1) sodium phosphate or (F-2) talc as a nucleating agent. Reference example Examples 1 to 12, which contained 0.01 to 0.5% by weight of (F-1) sodium phosphate, were particularly excellent in mechanical properties and electrical properties before and after impregnation. Reference example 11 had excellent mechanical and electrical properties as well as excellent surface appearance. reference Example 10, and (F-1) containing 0.8% by weight of sodium phosphate reference In Example 12, the mechanical properties were excellent, but the surface appearance showed a glass fiber floating phenomenon.

[0135] Specifically, in Comparative Example 1, which contained a small amount of (D)TPP, the electrical properties deteriorated before and after impregnation, and in Comparative Example 2, which contained an excessive amount of (D)TPP, the tensile strength before impregnation was less than 130 MPa, which did not satisfy the tensile strength required for automobile parts and electrical / electronic parts.

[0136] In addition, Comparative Examples 3 and 5, which did not contain (D)TPP and contained only (E) the copper-based composite heat stabilizer, showed deterioration in electrical properties before and after impregnation, and Comparative Example 4, which did not contain either (D)TPP or (E) the copper-based composite heat stabilizer, showed deterioration in tensile strength and electrical properties after impregnation.

[0137] In addition, in Comparative Example 6, which contained a small amount of (E) copper-based composite heat stabilizer, the flame retardancy decreased after impregnation, and in Comparative Example 7, which contained an excessive amount of (E) copper-based composite heat stabilizer, the electrical properties decreased both before and after impregnation.

[0138] In conclusion, it has been confirmed that the thermoplastic resin composition according to the present invention, which contains (A) polyamide resin, (B) glass fiber, (C) composite flame retardant, (D) phosphite-based heat stabilizer, and (E) copper-based composite heat stabilizer in a predetermined amount, achieves high flame retardancy by using a non-halogen phosphorus-based flame retardant, and has excellent mechanical and electrical properties even after absorbing moisture.

Claims

1. (A) 35 to 65% by weight of a polyamide resin; (B) 18 to 40% by weight of glass fibers; (C) 10 to 30% by weight of a composite flame retardant; (D) 0.06 to 0.4% by weight of a phosphite-based heat stabilizer; (E) 0.1 to 0.7% by weight of a copper-based composite heat stabilizer; (F) 0.05 to 0.6% by weight of a nucleating agent; The (F) nucleating agent is one or more phosphorus-containing nucleating agents selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, and salts and esters thereof; The (C) composite flame retardant comprises (c-1) an organic phosphinate metal salt and (c-2) a melamine phosphate flame retardant, The (E) copper-based composite heat stabilizer comprises at least one selected from the group consisting of copper chloride (I), copper bromide (I), copper iodide (I), copper chloride (II), copper bromide (II) and copper iodide (II), and an alkali metal halide.

2. The thermoplastic resin composition according to claim 1, characterized in that the thermoplastic resin composition has a comparative tracking index (CTI) of 530 V or more as measured on a 3 mm thick test piece according to IEC 60112 after being immersed in a water bath at 70° C. for 7 days.

3. The thermoplastic resin composition according to claim 1, wherein the polyamide resin (A) is at least one selected from the group consisting of a polymer of a diamine having 2 to 30 carbon atoms and a dicarboxylic acid having 4 to 30 carbon atoms; a lactam polymer; an aminocarboxylic acid polymer; and a copolymer of a lactam and an aminocarboxylic acid.

4. The thermoplastic resin composition according to claim 1, wherein the glass fibers (B) have an average diameter of 3 to 25 μm and an average length of 1 to 10 mm.

5. The thermoplastic resin composition according to claim 1, wherein the (c-1) organic phosphinate metal salt is a compound represented by the following Chemical Formula 1: 【Chemistry 1】 (The above R 1 and R 2 are each an alkyl group or an aryl group having 1 to 6 carbon atoms, M is at least one selected from the group consisting of Mg, Ca, Al, Sb, Sn, Ge, Ti, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, and a protonated nitrogen base, and n is an integer of 1 to 4.

6. The thermoplastic resin composition according to claim 1, wherein the (c-2) melamine phosphate-based flame retardant is at least one selected from the group consisting of melamine pyrophosphate, melamine polyphosphate, melamine pyrophosphate metal salts, and cyclic benzyl phosphate.

7. The thermoplastic resin composition according to claim 1, wherein the (D) phosphite-based heat stabilizer is at least one selected from the group consisting of triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis(3-methyl-6-t-butylphenyl-di-tridecyl) phosphite, cyclic neopentanetetrayl-bis(octadecyl) phosphite, tris(nonylphenyl) phosphite, tris(dinonyl) phosphite, dioctadecyl-3,5-di-t-butyl-4-hydroxybenzyl phosphonate, and di-n-octadecyl-1-(3,5-di-t-butyl-4-hydroxy-phenyl)-ethane phosphonate.

8. The thermoplastic resin composition according to claim 1, wherein the (D) phosphite-based heat stabilizer has a phosphorus content of 8 to 13 wt % based on the total weight of the thermoplastic resin composition.

9. (A) 35-65 wt% polyamide resin, (B) 18-40 wt% glass fiber, (C) 10-30 wt% composite flame retardant, (D) 0.06-0.4 wt% phosphite-based heat stabilizer, (E) 0.1-0.7 wt% copper-based composite heat stabilizer, and (F) 0.05-0.6 wt% nucleating agent, and kneading and extruding the mixture under conditions of 220-280° C. and 100-400 rpm to prepare pellets; The (F) nucleating agent is one or more phosphorus-containing nucleating agents selected from the group consisting of phosphoric acid, phosphorous acid, hypophosphorous acid, and salts and esters thereof; The (C) composite flame retardant comprises (c-1) an organic phosphinate metal salt and (c-2) a melamine phosphate flame retardant, The method for producing a thermoplastic resin composition, wherein the copper-based composite heat stabilizer (E) contains at least one selected from the group consisting of copper chloride (I), copper bromide (I), copper iodide (I), copper chloride (II), copper bromide (II), and copper iodide (II), and an alkali metal halide.

10. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Flame-retardant polyester composition

    JP1983017149A

  • Polyamide composition stabilized by copper salt and aromatic halogen compound

    JP2003518142A

  • Flame retardant-containing heat-aging polyamide

    JP2013508522A

  • Flame retardant polyamide resin composition and article comprising the same

    KR1020140086795A

  • Flame-Retardant Polyamide Composition

    US20160009918A1